2010
DOI: 10.1093/jxb/erq240
|View full text |Cite
|
Sign up to set email alerts
|

COI1, a jasmonate receptor, is involved in ethylene-induced inhibition of Arabidopsis root growth in the light

Abstract: Plant response to stress is orchestrated by hormone signalling pathways including those activated by jasmonates (JAs) and by ethylene, both of which stunt root growth. COI1 is a JA receptor and is required for the known responses to this hormone. It was observed that the coi1 mutant, which is largely unresponsive to growth inhibition by JAs, was also partially unresponsive to growth inhibition by ethylene and by its immediate precursor, 1-aminocyclopropane-1-carboxylic acid (ACC), in the light but not in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 87 publications
(120 reference statements)
4
54
0
1
Order By: Relevance
“…The comparison of the effect of MeJA and the role of COI1 in root cells and root hair cells would suggest that COI1 has a differential role in mediating endoreduplication and/or cell expansion. This is also consistent with data showing that COI1 was required for 1-aminocyclopropane-1-carboxylic acid-induced root growth inhibition but was not required for 1-aminocyclopropane-1-carboxylic acidinduced root hair elongation (Adams et al, 2010). The quantification of nuclear surface area with H2B-YFP showed that the endocycle is initiated farther away from the QC (Fig.…”
Section: Meja Reduces Both Cell Division and Cell Expansion And Delaysupporting
confidence: 92%
See 1 more Smart Citation
“…The comparison of the effect of MeJA and the role of COI1 in root cells and root hair cells would suggest that COI1 has a differential role in mediating endoreduplication and/or cell expansion. This is also consistent with data showing that COI1 was required for 1-aminocyclopropane-1-carboxylic acid-induced root growth inhibition but was not required for 1-aminocyclopropane-1-carboxylic acidinduced root hair elongation (Adams et al, 2010). The quantification of nuclear surface area with H2B-YFP showed that the endocycle is initiated farther away from the QC (Fig.…”
Section: Meja Reduces Both Cell Division and Cell Expansion And Delaysupporting
confidence: 92%
“…MeJA inhibits the elongation of the cells in Col gl1 and aos (63% and 67%, respectively), although to a lower extent with respect to the entire root organ. In coi1-16B, the elongation of the cell was inhibited about 36%, in agreement with previous reports (Adams et al, 2010). While the root hair distribution was not obviously affected by the mutations analyzed or by MeJA treatment, the length of fully elongated root hairs in the mature region was also negatively affected by MeJA treatment (Supplemental Fig.…”
Section: Meja Negatively Affects Cell Cycle Progression During Leaf Dsupporting
confidence: 91%
“…It was recently reported that root growth inhibition by ET was more pronounced in the two JA-Ile biosynthesis mutants dde2-2 and opr3 as compared with coi1-16 (Adams and Turner, 2010), establishing another example for a JA-Ile-independent COI1 activity.…”
Section: Coi1 Enhances Stress-induced Cyp81d11 Promoter Activity Evenmentioning
confidence: 95%
“…ORA59 is an essential integrator of the jasmonate and ethylene signal transduction pathways (Pre et al 2008). The jasmonate receptor COI1 is involved in ethylene-induced inhibition of Arabidopsis root growth in the light (Adams and Turner 2010). In contrast, ethylene inhibits the expression of some jasmonate-responsive genes encoding vegetative storage proteins (VSPs) and a thionin (Thi1.2) (Rojo et al 1999;Norman-Setterblad et al 2000;Ellis and Turner 2001), and jasmonates suppress ethylene-induced hypocotyl hook formation in the triple response in a COI1-dependent manner (Ellis and Turner 2002).…”
Section: Relationship Between Jasmonates and Ethylene In The Control mentioning
confidence: 99%